PENGEMBANGAN MATERI ATLETIK MELALUI PERMAINAN ATLETIK JALALOLE UNTUK SISWA SD KELAS IV - RIMA FEBRIANTI (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2015)
Development Athletics Learning Throught Athletics Jalalole of Â Elementary Students. Basically, 4th grade students of elementary school have high tension to play, therefor, sport and health education teacher should be able to develop more interesting teaching model that make students enjoy the process more. Result of the research shows that students' interest and tension on 3 in 1 athletic game is 52,21% higher than conventional process, students' activeness or physical intensity is improve up to 71% brings maximum number of heart pulse Model's quality improve tools and equipment's appropriateness level up into 75% so that graded as good. In three scope of sport and health education, the cognitive and psycho-motor aspects include in high class category while affecting aspect is included in the middle level. And to value the spirit and confidence in the good category, while the value of sportive and honesty in the medium category. The conclusion of this research is that the product of 3 in 1 athletic game is appropriate and acceptable or practicable in sport and health education's athletic material learning for IV grader of elementary